Boosting the photocatalytic H2 evolution activity of Fe2O3 polymorphs (α-, γ- and β-Fe2O3) by fullerene [C60]-modification and dye-sensitization under visible light irradiation. Issue 46 (5th June 2017) - Song, Ting; Zhang, Piyong; Zeng, Jian; Wang, Tingting; Ali, Atif; Zeng, Heping
Abstract : Different morphologies of Fe2 O3 polymorphs were constructed and modified by fluorescein sensitization and C60 cocatalyst to prepare highly active photocatalysts. Abstract : C60 /Fe2 O3 nanocomposites are successfully prepared, well characterized, and employed in visible-light-driven photocatalytic H2 production. The Fe2 O3 polymorphs show obvious broad-spectrum absorption, even close to the near infrared region (780–900 nm). The H2 production rates of β-Fe2 O3 and γ-Fe2 O3 are almost 2.1 times and 3.1 times higher than α-Fe2 O3 (which itself is close to that of g-C3 N4 ). This demonstrates that carefully controlling the polymorphs can tune the photocatalysts' H2 production properties. After modifying the Fe2 O3 polymorphs with C60, the sample with 0.5 wt% C60 /β-Fe2 O3 has the optimum photocatalytic activity. This result indicates that the strength of the interaction and interfacial contact between C60 and Fe2 O3 polymorphs plays an important role in the enhancement of photocatalytic activity, which can improve the transmission efficiency of photogenerated electrons via a conjugated three-dimensional π system. Fluorescein is introduced as a photosensitizer and the optimum mass ratio of fluorescein + 0.5C60 /β-Fe2 O3 is 1 : 1, which significantly boosts the photocatalytic H2 evolution rate of 0.5C60 /β-Fe2 O3 from 321.8 to 1665.0 μmol g −1 h −1 . Meanwhile, the composites exhibit high stability and reusability.